VISUAL BASIC VERSION 6.0 APPLICATION FOR ADMISSION IN RESERVATION SYSTEM PT.ABC - Nugroho Budi Santoso; Lingga Hermanto, SSi, MMSI (Jurnal Sistem Informasi, 2003)
Writing is about the problems that arise in the ticket reservation system. The authorproposes an application to solve the problem while improving service quality ticketreservation system.With this application you can quickly find out which seats are still vacant so as tospeed the process of ticket reservation services. Attached to the end writing programsto support the application.